2006
DOI: 10.1159/000095552
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis and Exposure to Environmental Toxins: An Australian Case-Control Study

Abstract: It has been suggested that environmental toxins could be risk factors for sporadic amyotrophic lateral sclerosis (SALS). We therefore analysed epidemiological data on 179 SALS cases and 179 age-, ethnicity- and sex-matched controls in Australia using self-reporting questionnaires. SALS was associated with solvent/chemical exposure (OR = 1.92, 95% CI: 1.26–2.93), overall herbicide/pesticide exposure (OR = 1.57, 95% CI: 1.03–2.41) and industrial herbicide/pesticide exposure (OR = 5.58, 95% CI: 2.07–15.06). Expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 50 publications
7
41
2
Order By: Relevance
“…Our findings confirm results of previous research suggesting a potential relationship between exposure to metals [11,12,13,14,15,16,17] and pesticides [23,35,38,39] and risk of ALS. Although not causally related, lead has been the most consistent environmental risk factor over time [11,13,16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings confirm results of previous research suggesting a potential relationship between exposure to metals [11,12,13,14,15,16,17] and pesticides [23,35,38,39] and risk of ALS. Although not causally related, lead has been the most consistent environmental risk factor over time [11,13,16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Emerging evidence links sporadic ALS to agricultural chemicals (66), PON genotype (67), and perhaps genotype/pesticide interactions (68), compatible with a link between OPs and excess ALS in GWV. Parkinson's disease, a related neurodegenerative condition, has also been linked to pesticides (69,70) and PON genotype (26,71), suggesting that monitoring for excess age-adjusted Parkinson's in GWV may be prudent.…”
Section: Enzymes That Help Detoxify Acheis Differ In Ill Veterans Vsmentioning
confidence: 99%
“…There was an increased risk of ALS among employees of the Dow Chemical Company who were exposed to the herbicide 2,4-dichlorophenoxyacetic acid versus other Dow employees (Burns et al, 2001). Similar studies have found positive associations for populations exposed to pesticides (McGuire et al, 1997;Qureshi et al, 2006), and the relationship was found to be dependent on dose (Morahan & Pamphlett, 2006). Overall, the relationship tends to be stronger for males than females (McGuire et al, 1997;Morahan & Pamphlett, 2006).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 66%
“…Similar studies have found positive associations for populations exposed to pesticides (McGuire et al, 1997;Qureshi et al, 2006), and the relationship was found to be dependent on dose (Morahan & Pamphlett, 2006). Overall, the relationship tends to be stronger for males than females (McGuire et al, 1997;Morahan & Pamphlett, 2006). In one study using participants in the American Cancer www.intechopen.com Society's Cancer Prevention Study II, no association between pesticide exposure and ALS was detected (Weisskopf et al, 2009).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 70%